Work Stress Factors in Innures at the Putri Hijau Kesdam I Bukit Barisan Medan - Agung Prawira; Ismail Effendi; Miskah Afriani (Journal La Medihealtico, 2021)
One of the jobs that is prone to stress is a nurse. According to PPNI, 50.9% of Indonesian nurses experience work stress. This study was to determine the factors that influence the stress of nurses at the Putri Hijau Level II Hospital, Medan. The research design used was cross sectional with a population of 152 nurses in this study and the sample used a stratified random sampling technique to 60 nurses. Data analysis using binary logistic regression test. Research shows that there is an effect of workload (p = 0.03) and interpersonal relationship (p = 0.03) on nurses 'work stress, while the variables of gender, tenure, career development and role conflict have no effect on nurses' work stress. Workload and interpersonal relationships in the workplace have the potential to cause work stress for nurses. So it is advisable for the management to adjust the physical and mental workload with the capacity and ability of nurses, and strive for a conducive social environment.